2019
DOI: 10.1108/ccsm-02-2019-0044
|View full text |Cite
|
Sign up to set email alerts
|

Unbundling dynamic capabilities for inter-organizational collaboration

Abstract: Purpose The purpose of this paper is to explore two distinct subsets of dynamic capabilities that need to be deployed when pursuing innovation through inter-organizational activities, respectively, in the contexts of broad networks and specific alliances. The authors draw distinctions and explore potential interdependencies between these two dynamic capability reservoirs, by integrating concepts from the theoretical perspectives they are derived from, but which have until now largely ignored each other – the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 103 publications
(127 reference statements)
0
16
0
Order By: Relevance
“…MNEs need to protect their IP in broader ecosystems with multiple linkages and boundary-spanning activities. This will require specialized collaborative capabilities for managing complex constellations of boundaryspanning, inter-firm relationships (Petricevic & Verbeke, 2019). The DCs required for designing and shaping networks of multiple stakeholder relationships (Rowley, 1997) and across multiple embeddedness dimensions (Ferraris, 2014) thus become especially hard to achieve with amplified VUCA (Helfat et al, 2007: 7), as suggested by the third-order cascading effects in Figure 1.…”
Section: Dynamic Capabilities For Managing New Ib Realitiesmentioning
confidence: 99%
“…MNEs need to protect their IP in broader ecosystems with multiple linkages and boundary-spanning activities. This will require specialized collaborative capabilities for managing complex constellations of boundaryspanning, inter-firm relationships (Petricevic & Verbeke, 2019). The DCs required for designing and shaping networks of multiple stakeholder relationships (Rowley, 1997) and across multiple embeddedness dimensions (Ferraris, 2014) thus become especially hard to achieve with amplified VUCA (Helfat et al, 2007: 7), as suggested by the third-order cascading effects in Figure 1.…”
Section: Dynamic Capabilities For Managing New Ib Realitiesmentioning
confidence: 99%
“…This result is in line with our hypothesis and the previous literature discussing that network connections create a network community that results in higher synergy among firms and achievement of more second-order capabilities (c.f. McCormack et al, 2002 ; Petricevic & Verbeke, 2019 ).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…A combination of economic forces and social exchange opportunities in the business ecosystem promotes value co-creation (Kohtamäki & Rajala, 2016 ). The literature provides supportive evidence that the dynamic capabilities create synergies for inter-connected firms at the network level and the firm level (Petricevic & Verbeke, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collaboration in organizations is crucial in creating and capturing value (Petricevic & Verbeke, 2019). However, collaborative innovations fail for numerous reasons, for example, lack of funding, clarity over each stakeholder’s responsibility or the absence of commitment (Martynov, 2019; Porter & Birdi, 2018).…”
Section: Literature Background: Collaboration and Innovation In The Context Of The Aviation Sectormentioning
confidence: 99%